VersaCAD for Macintosh. - Snoonian, Deborah (Architectural Record, 2005)
This article reports that VersaCAD introduced by Archway Systems Inc. has been available for Macs and Windows-based computers for several years, but the developers launched a new version a few months ago designed to run on Macs using OS version 10.3 or later. The software takes advantage of the Mac's graphical interface and offers users the ability to import files created in AutoCAD and other programs. Other features include an extensive library of symbols and a special pulldown menu for architectural drawings, with functions handy for creating doors and windows.